2004
DOI: 10.1097/01.icu.0000134878.48361.50
|View full text |Cite
|
Sign up to set email alerts
|

Management of childhood glaucoma

Abstract: Continued progress in understanding the genetics of childhood glaucoma and the selection of effective surgical procedures highlight progress reported in the last year and should assist with decision making for children with childhood glaucoma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 22 publications
0
5
0
Order By: Relevance
“…It remains an important cause of childhood blindness (3, 7, 8). Primary congenital glaucoma is a recognizable clinical problem in Saudi Arabia, absorbing a significant amount of clinical resources (9) with significant morbidity, leading to lifelong visual disability (10, 11). Some studies revealed that PCG appears in a more severe form in Saudi Arabia than in Western countries (12).…”
Section: Introductionmentioning
confidence: 99%
“…It remains an important cause of childhood blindness (3, 7, 8). Primary congenital glaucoma is a recognizable clinical problem in Saudi Arabia, absorbing a significant amount of clinical resources (9) with significant morbidity, leading to lifelong visual disability (10, 11). Some studies revealed that PCG appears in a more severe form in Saudi Arabia than in Western countries (12).…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, autosomal dominant transmission has been reported with incomplete or variable penetrance 18 . Nevertheless, most cases appear to be caused by multi‐factorial inheritance 1,3,6,17,19 …”
Section: Discussionmentioning
confidence: 99%
“…Medical therapy alone controls childhood glaucoma infrequently and surgery is often needed 19 . When skilfully performed, incisional surgeries such as goniotomy and trabeculotomy are effective because they can reduce the resistance to aqueous outflow created by the structural abnormalities in the anterior chamber angle 3,6 .…”
Section: Discussionmentioning
confidence: 99%
“…Most occurrences of JOAG are first recognized between the ages of 5 and 18 years. 1 It does not cause enlargement of the cornea or breaks in Descemet membrane as seen in more common primary congenital glaucoma. JOAG is always bilateral, but may be worse in one eye than the other.…”
mentioning
confidence: 99%